How rising income inequality influenced economic growth in Germany - Hanne Albig; Marius Clemens; Ferdinand Fichtner; Stefan Gebauer; Simon Junker; Konstantin Kholodilin (DIW Economic Bulletin, 2017)
The cumulative growth rate of the German economy since reunification would have been around two percentage points higher if income inequality had remained constant. This is whatsimulations using the DIW Macroeconomic Model have shown. They were made under the assumption that the income distribution dynamics would not be influenced by any feedback effects of economic growth. In 2015, Germany's real GDP should have been 40 billion euros higher than it actually was. Private consumer demand, investment, and exports would all have risen faster if inequality - here measured by the Gini index of net household income - had remained at its 1991 level. At the same time, the trade surplus would not have grown asquickly. In fact, it curbed the effect of income inequality on GDP. The finding is not only relevant given the debate over imbalances in the euro area. It also clearly indicates that the discussion about the macroeconomic consequences of rising income inequality has excessively focused on its negative effects on GDP. Private consumption, infinitely more important to the German population's quality of life, will decline more sharply in the long run.
Keywords: D31; E27; O15; 330; income distribution; economic growth; macroeconomic imbalances